Unmet Need for Family Planning in Indonesia and Its Associated Factors - Nuryana, Dewi; Cahyani, Restu Adya; Rahayu, Sukma; Romadlona, Nohan Arum; Liyanto, Elvira; Daisy, Lovely; Hartiti, Wira; Ratnawati, Maria Evi; Utomo, Budi; Magnani, Robert Joseph (UI Scholars Hub, 2023)
Background: The unmet need for family planning in Indonesia has been stagnant since the early 2000s in the 10%–12% range with substantial socioeconomic and geographic disparities. This study sought to better understand the factors underlying the nonuse of contraceptives among women with an apparent need for family planning so that evidence-based corrective actions can be taken. Methods: Three sources of quantitative data were used in the study—the 2017 Indonesia Demographic Health Survey, the 2018 Village Potential Survey, and the National Population and Family Planning Board service statistics. Further insights were obtained from online focus group discussions and in-depth interviews with participants in 12 districts/cities in seven provinces. Results: The analyses indicated that health concerns, service delivery-related factors, and opposition to family planning all contribute to the unmet need for family planning in Indonesia. Importantly, the salience of these factors varied significantly across different subgroups of women and geographic areas. Conclusions: Successful efforts to reduce the unmet need for family planning are complex in that they must contend with the interplay between local sociocultural contexts, individual beliefs/aspirations/preferences, and the supply environment of family planning services. Differentiated interventions for different population subgroups and geographic areas will be needed.